2016
DOI: 10.18632/aging.100893
|View full text |Cite
|
Sign up to set email alerts
|

The signaling pathways by which the Fas/FasL system accelerates oocyte aging

Abstract: Abstract:In spite of great efforts, the mechanisms for postovulatory oocyte aging are not fully understood. Although our previous work showed that the FasL/Fas signaling facilitated oocyte aging, the intra-oocyte signaling pathways are unknown. Furthermore, the mechanisms by which oxidative stress facilitates oocyte aging and the causal relationship between Ca 2+ rises and caspase-3 activation and between the cell cycle and apoptosis during oocyte aging need detailed investigations. Our aim was to address thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Calcium is a major signaling molecule that regulates many aspects of cellular function, including cell‐cycle progression (Machaty, ; Tosti, ), cell‐cycle arrest (Tripathi et al, ), and apoptosis (Berridge et al, ; Tiwari et al, ). A sustained increase in [Ca 2+ ] i levels beyond the normal physiologic range in oocytes triggers FAS‐ligand‐ and mitochondria‐mediated apoptosis in several mammalian species (Tiwari, Prasad, Shrivastav, & Chaube, ; Zhu et al, ). Previous studies suggested that the physiological role of calcium depends on its intracellular concentration (Homa, ; Naik & Pardasani, ; Tosti, ; Whitaker, ), resulting in improved developmental competence or fragmentation/apoptosis (Takahashi et al, ; Takahashi, Saito, Hiroi, Doi, & Takahashi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is a major signaling molecule that regulates many aspects of cellular function, including cell‐cycle progression (Machaty, ; Tosti, ), cell‐cycle arrest (Tripathi et al, ), and apoptosis (Berridge et al, ; Tiwari et al, ). A sustained increase in [Ca 2+ ] i levels beyond the normal physiologic range in oocytes triggers FAS‐ligand‐ and mitochondria‐mediated apoptosis in several mammalian species (Tiwari, Prasad, Shrivastav, & Chaube, ; Zhu et al, ). Previous studies suggested that the physiological role of calcium depends on its intracellular concentration (Homa, ; Naik & Pardasani, ; Tosti, ; Whitaker, ), resulting in improved developmental competence or fragmentation/apoptosis (Takahashi et al, ; Takahashi, Saito, Hiroi, Doi, & Takahashi, ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that high level of [Ca ++ ]i trigger generation of ROS and mitochondria‐mediated apoptosis in mammalian oocytes. The involvement of increased [Ca ++ ]i level has also been reported to trigger Fas ligand‐mediated apoptosis in mouse oocytes (Zhu et al, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
“…Growing body of evidences suggest that sustained high cytosolic free Ca ++ level induces CaMKII activity (Olofsson et al, ; Zhu et al, ) and trigger generation of ROS (Tripathi and Chaube, ) sufficient enough to cause oxidative stress (OS) in aged oocytes cultured in vitro (Gordo et al, ; Chaube et al, ; Martin‐Romero et al, ; Tripathi and Chaube, ). Further, CaMKII activates Wee 1 that induces Thr14/Tyr15 phosphorylation of Cdk1 and cyclin B1 degradation leading to MPF destabilization (Kubiak et al, ; Oh, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
See 2 more Smart Citations